(untitled) (Research Journal of Padmakanya Multiple Campus, 2024)
The characters of the Mahabharata encounter moral crisis across various contexts. This paper attempts to explore and analyze different episodes of moral dilemmas faced by the major characters. Even the wise and mighty characters hesitate while making their choices. The conflict of right action is an existential problem. This situation is created when a person is caught between ideal and practical, family and society, kinship and friendship, desire and duty, and worldliness and spirituality and so on. The objectives of this paper are: to know the causes of the moral crisis and to find the reasons why people face difficulty in doing right action. I have used the method of textual analysis in this paper. The conceptual framework consists of theories of moral crisis/dilemma. I have also used the philosophies of law of karma/duty, attachments and renunciation from the Bhagavad-Gita. The findings are: the characters’ attachments have caused their moral dilemmas in doing right action. Self-control is the key to triumph over moral crisis. The consequence of right thinking is right action.